Pengaruh Tingkat Kesehatan Terhadap Profitabilitas BPR Provinsi Kepri - Hesniati Hesniati; Novilia Novilia (Journal of Global Business and Management Review, 2019)
This research is examining CAMEL ratio effects profitability of rural banks. The population in this study is rural banks in Riau Island Province listed in the Indonesia Financial Service Authority in 2012 until 2016. Samples were taken by using purposive sampling method. Total samples used in this research are 23 companies with total observation 115 data. The data obtained will be tested with regression panel method. The result showed that variables of BOPO, Cash Ratio, and NPL are significant negative with the profitability. KAP and LDR are insignificant with profitability of rural banks.